Realization of the land banking in the Republic of Moldova as a strategic objective in the sustainable rural development - Iurie Danilov; Petru Tomita; Anatol Racul (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Agricultural land consolidation represents a complex of organizational, technical, economic, ecological and other legal measures requested by the rural community for the purpose of the most rational, efficient use and exploitation of land, as a whole and as a result, raising the living standard in rural communities. The creation of the Commercial Land Bank in the Republic of Moldova requires the consolidation of land and becomes a necessity even in conditions of private ownership over agricultural land, in conditions of wider structural reforms. The reasons for agricultural land consolidation, at present, are much deeper than its privatization. The research presents the basic structure and criteria in the organization of banking activity in the agricultural sector including the financial insurance of land transactions according to the nonparametric rating of data envelopement analysis.
Keywords: Q14; R14; R30; 330; land consolidation; land fragmentation; land bank; data envelopment analysis; european size unit